1995
DOI: 10.1126/science.270.5237.789
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant Subcellular Localization of BRCA1 in Breast Cancer

Abstract: The BRCA1 gene product was identified as a 220-kilodalton nuclear phosphoprotein in normal cells, including breast ductal epithelial cells, and in 18 of 20 tumor cell lines derived from tissues other than breast and ovary. In 16 of 17 breast and ovarian cancer lines and 17 of 17 samples of cells obtained from malignant effusions, however, BRCA1 localized mainly in cytoplasm. Absence of BRCA1 or aberrant subcellular location was also observed to a variable extent in histological sections of many breast cancer b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
182
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(196 citation statements)
references
References 23 publications
12
182
2
Order By: Relevance
“…21,22 Mutant forms of BRCA1 that occur in breast and ovarian cancer localize, how- ever, to the cytoplasm. 20 Similar mis-transport has been demonstrated for transcription factors involved in oncogenesis such as c-Fos and SV40 large T antigen. [23][24][25] We have previously demonstrated aberrant localization of F1␤ ATPase, the catalytic subunit of mitochondrial ATP synthase, to the plasma membrane of tumor cell lines.…”
Section: Semiquantitative Analysis Of P385 Gene Transcriptionsupporting
confidence: 53%
See 1 more Smart Citation
“…21,22 Mutant forms of BRCA1 that occur in breast and ovarian cancer localize, how- ever, to the cytoplasm. 20 Similar mis-transport has been demonstrated for transcription factors involved in oncogenesis such as c-Fos and SV40 large T antigen. [23][24][25] We have previously demonstrated aberrant localization of F1␤ ATPase, the catalytic subunit of mitochondrial ATP synthase, to the plasma membrane of tumor cell lines.…”
Section: Semiquantitative Analysis Of P385 Gene Transcriptionsupporting
confidence: 53%
“…Though BRCA1 is expressed at normal levels in breast cancer it is however translocated to an abnormal cellular site. 20 The wild-type BRCA1 gene product normally localizes to the nucleus via 2 putative signal peptides that are similar to steroid hormone receptor molecules. 21,22 Mutant forms of BRCA1 that occur in breast and ovarian cancer localize, how- ever, to the cytoplasm.…”
Section: Semiquantitative Analysis Of P385 Gene Transcriptionmentioning
confidence: 99%
“…The glycine generated by the exon 11 ± 12 junction ( Figure 1d) is maintained in the exon 11a ± 12 splice, thereby preserving the normal reading frame of exons 12 ± 24. Exon 11b encodes two putative nuclear localization elements previously noted in BRCA1 (Chen et al, 1995). Thus, one of the most signi®cant functional consequences of the exon 11b alternative splice is the potential generation of an obligate cytoplasmic BRCA1 variant.…”
Section: Isolation Of Brca1 Clonesmentioning
confidence: 99%
“…These ®ndings support tumor suppressive roles for alternatively spliced BRCA1 variants containing the N and C terminal exons. Chen et al (1995Chen et al ( , 1996 have published data demonstrating that BRCA1 is a nuclear protein in normal cells, whereas the protein was aberrantly located in the cytoplasm in breast and ovarian cancer cells. In contrast, Scully et al (1996) have found that BRCA1 is exclusively nuclear regardless of cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Since neoplastic development in BRCA1 mutation carriers is accompanied by loss or inactivation of the wildtype allele, the BRCA1 protein is likely to function as a tumor suppressor (Smith et al, 1992). Although the biochemical properties of BRCA1 are poorly understood, recent studies have shown that its subcellular distribution is cell cycle-dependent (Chen et al, 1995(Chen et al, , 1996Scully et al, 1996Scully et al, , 1997aThomas et al, 1996;Ru ner and Verma, 1997;Thakur et al, 1997;Wilson et al, 1997). BRCA1 polypeptides are di usely distributed in the nuclei of resting cells and G1 proliferating cells.…”
mentioning
confidence: 99%